Advances in nanoparticles-based approaches in cancer theranostics - Muhammad Akmal Raheem; Muhammad Ajwad Rahim; Ijaz Gul; Xiaoyun Zhong; Chufan Xiao; Haihui Zhang; Jiazhang Wei; Qian He; Muhammad Hassan; Can Yang Zhang; Dongmei Yu; Vijay Pandey; et al. (Elsevier, 2023)
In recent years, the incidence and mortality rate of cancer is raising worldwide. Traditional approaches for cancer patient management including surgery, chemotherapy, radiotherapy, and targeted therapies provide unsatisfactory results and are often associated with adverse reactions. Over the last few decades, nanotechnology has been a rapidly emerging area of theragnostic in clinical research. It plays a vital role as a bridge between the science and technology of miscellaneous nanoparticles (NPs) and nanomedicine. In general, NPs with a range of sizes of 1-100 nm are thought to be acceptable for cancer medications. NPs may enhance the consistency and solubility of therapeutic drugs to obtain site-specific targeting, controlled release, and safe for healthy organs. NPs have the benefit of pathophysiological properties, enhanced permeability and retention (EPR) effects, and an advantage in cancer targeting. Furthermore, theranostic nanoparticles have been established having incorporated diagnostics and therapy in a single system that might provide more personalized treatment with optimal doses and monitoring the distribution, targeting, and response to therapy by using imaging tools. In this review, we have discussed the classes of nanoparticles, targeting approaches, and implications of NPs for cancer theranostics with recent examples.